The implementation of Ingrated Management Systems in Mopani District secondary schools, Limpopo Province - Malema, Pinny Wisani (University of Limpopo (Turfloop Campus), 2013)
The South African government, through the Department of Education is continually seeking means and strategies to improve the quality of education in the country. Integrated Quality Management System (IQMS) is one of the systems adopted and implemented in all public schools to improve the quality of teaching and learning in schools. IQMS, as outlined in Collective Agreement No 8 of 2003, was informed by the Employment of Educators Act 76 of 1998 and the Constitution of the Republic of South Africa. IQMS consists of three programmes which need to be in place in order to enhance and monitor performance of the education system. Developmental Appraisal’s purpose is to appraise individual educators in a transparent manner with a view to determining areas of strengths and weaknesses and to draw up programmes for individual development; Performance Measurement’s purpose is to evaluate individual educators for salary and grade progression, affirmation of appointments and rewards and incentives, and Whole School Evaluation’s purpose is to evaluate the effectiveness of a school. The research focused on how IQMS is implemented in Mopani District secondary schools, in Limpopo Province, South Africa. Qualitative research methodology was used. Results indicated that some structures and individuals know their roles and responsibilities in IQMS implementation; however, they admit to encountering challenges in implementing it. Educators and structures generally perceive IQMS positively and believe that educator performance may improve if the challenges encountered are addressed by the Department of Education. Recommendations were also advanced on how to make IQMS serve the purpose for which it was intended.
Thesis (MPA.) -- University of Limpopo, 2013
Keywords: Quality management systems; Quality of teaching; Teacher performance; 658.4013071; School management and organisation; Integration in education